Otimização do processo de revestimento do medicamento cloridrato de ciclobenzaprina - Barbosa, Marlize Fernandes (2025)
The treatment of diseases through drugs predates written history, starting with drugs of natural origin, extracted mainly from plants and some minerals, up to the current highly technological drugs. Historically, the drug cyclobenzaprine hydrochloride has been used to treat several diseases, however, with the advancement of studies, it is currently recognized as a muscle relaxant. Drugs are inserted into the human body through numerous routes of admission, the most requested by the patient being the oral route, and can be administered in the form of tablets. In order for the drug to become a tablet, transformation processes are necessary: granulation, compression and coating. In this work, the best parameters to obtain a more robust and optimized coating were evaluated through a 2³ factorial design, evaluating how the input variables: air flow, pump speed and basket speed influence the response variables weight gain and process time. Based on the experiments, it was possible to obtain a multiple linear regression model with R² of 0.984 and 0.985 respectively, that is, the model found efficiently describes the process behavior. Furthermore, based on the data analysis, it was verified that the three parameters evaluated have an influence on the weight gain, mainly the basket speed and pump speed, for the process time response variable, the significant parameter is the pump speed. A colorimetric evaluation method, based on RGB, was also proposed and implemented, which was able to identify variations in the color of the tablets and with it, it was possible to prove that all the parameter configurations tested were able to provide uniform coloration among the tablets.